DIVERSI TERHADAP ANAK DALAM PERKARA TINDAK PIDANA OLEH UNIT PELAYANAN PEREMPUAN DAN ANAK POLRES BOYOLALI - PURWADI, JOKO (Dinamika Hukum, 2019)
Diversion is the transfer of settlement of child cases from criminal justice processes to processes outside the court to protect children from the negative stigma of a long judicial process starting from investigation, prosecution and court examination. This study examines and analyzes the diversion process for children in criminal cases by the Unit The method used is empirical juridical research because this research is related and has a starting point on the aspects of positive law or current law, in the form of statutory provisions which are then related to practice in the field which is a social reality and behavior of the apparatus investigator in the implementation of diversion Keywords: Criminal Acting Children, Diversion, Women's and Children's Services Unit